Этнокультурный центр «Евразия» как среда самопознания, самосовершенствования учащихся общеобразовательной школ - Артёмова, Е.М. (My University, 2013)
Ethnocultural center "Eurasia" – is an integral social organism functioning when the major components of education interact with each other, reflecting a particular way of life the school orga- nization.Ethnocultural center "Eurasia" could be a model for the school educational system.